TIME-CONSTRAINS PROJECT SCHEDULING PROBLEM WITH ACTIVITIES ALTERNATIVES, ANT COLONY OPTIMIZATION APPROACH - Showkat, Faiz Faiq (Al-Nahrain Journal of Science, 2009)
In this paper we handle the problem of scheduling/rescheduling project activities when there is more than one method (alternatives) available to execute the project activities, each method has its own time duration and resource requirements and also there is a dependency between the methods of execution the activities , A suggested method is presented here to deal with activities dependency and the ant colony optimization metaheuristic approach is used to find the best set of alternatives for the project activities in order to finish the project as soon as possible and identifying the critical path of the project.